Clinical and radiographic evaluation of Bio-Gen with biocollagen compared with Bio-Gen with connective tissue in the treatment of class II furcation defects: a randomized clinical trial - Niloofar Jenabian; Sina Haghanifar; Avideh Maboudi; Ali Bijani (University of São Paulo, 2013)
OBJECTIVE: Treatment of furcation defects are thought to be challenging. The purpose of this study was to evaluate the clinical and radiographic parameters of Bio-Gen with Biocollagen compared with Bio-Gen with connective tissue in the treatment of Class II furcation defects. MATERIAL AND METHODS: In this clinical trial, 24 patients with Class II furcation defect on a buccal or lingual mandibular molar were recruited. After oral hygiene instruction, scaling and root planing and achievement of acceptable plaque control, the patients were randomly chosen to receive either connective tissue and Bio-Gen (case group) or Biocollagen and Bio-Gen (control group). The following parameters were recorded before the first and re-entry surgery (six months later): vertical clinical attachment level (VCAL), gingival index (GI), plaque index (PI), horizontal probing depth (HPD), vertical probing depth (VPD), gingival recession (GR), furcation vertical component (FVC), furcation to alveolar crest (FAC), fornix to base of defect (FBD), and furcation horizontal component (FHC) were calculated at the time of first surgery and during re-entry. A digital periapical radiograph was taken in parallel before first surgery and re-entry. The radiographs were then analyzed by digital subtraction. The differences with p value <0.05 were considered significant. RESULTS: Only the mean changes of FAC, FHC, mean of FHC, FBD in re-entry revealed statistically significant differences between the two groups. HPD, VPD, FBD, FAC, and FHC showed statistically significant differences after 6 months in the case group. However, in the control group, statistically significant differences were found in GR and HPD. We did not observe any significant difference in radiographic changes among the two groups. CONCLUSION: The results of this trial indicate that better clinical outcomes can be obtained with connective tissue grafts in combination with bone material compared with a resorbable barrier with bone material. The differences in radiographic changes between the two groups, however, were not statistically significant.